Physical simulation experiments on competitive dissolution of helium in helium-containing to helium-rich gas reservoirs - Yi ZOU; Qingyong LUO; Jianfa CHEN; Huayao ZOU; Tao DU; Xiaoqiang LIU; Xinyong CAI; Chengming YU; Zilong FANG (Meitian dizhi yu kantan)
Background and Purpose Helium is widely applied in high-tech and scientific research fields due to its unique physicochemical properties. Formation water plays a key role in helium migration and enrichment. Typically, in the form of dissolved gas, helium is transported in pores or fractures by formation water. When helium-rich fluids migrate to shallow natural gas reservoirs, helium will experience dissolution and desorption exchange with other gases. This process is affected by formation temperature, pressure, and water salinity, as well as the competitive dissolution between helium and other gases. However, there is a lack of studies on the mechanisms underlying the competitive dissolution between helium and other gases under formation conditions, along with the impact of these mechanisms on helium enrichment in helium-containing and helium-rich natural gas reservoirs.MethodsThis study investigated the Jinqiu gas field in the Sichuan Basin—a helium-containing to helium-rich gas field discovered recently. Based on actual geological data on gas reservoirs in this gas field, this study conducted physical simulation experiments by setting varying temperature, pressure, and water salinity conditions. Accordingly, delved into the mechanisms behind the competitive dissolution between helium and other gases, as well as the impact of these mechanisms on helium enrichment in natural gas reservoirs.Results and ConclusionsUnder pressure and temperature ranges of 10–60 MPa and 20–150 ℃, respectively, helium solubility in formation water with identical salinity initially decreased and then increased with rising temperature but kept increasing with pressure. Under a pressure of 25 MPa and a temperature of 70 ℃, the helium solubility decreased significantly with an increase in formation water salinity (0‒300 g/L). Furthermore, under pressures ranging from 10 MPa to 60 MPa, temperatures varying from 20 ℃ to 150 ℃, and a formation water salinity of 84.5 g/L, a higher proportion of helium in mixed gases of helium and nitrogen corresponded to a higher helium solubility in the formation water. The helium accumulation in gas reservoirs in the Jinqiu gas field is primarily affected by the following factors: (1) Decreases in the formation temperature and pressure, combined with hydrocarbon enrichment attributable to hydrocarbon generation from organic matter, jointly decrease helium solubility in formation water, leading to helium exsolution from the formation water. (2) Hydrocarbon gases transport helium to shallower reservoirs. During the migration, further decreases in the formation temperature and pressure accelerate helium exsolution from the formation water. The resulting helium, together with hydrocarbon gases, recharges shallow gas reservoirs. This process results in higher helium content in shallow reservoirs compared to deep ones. (3) Gas reservoirs with anomalously low pressures exhibit lower gas recharge intensity than those with anomalously high and normal pressures, producing a smaller helium dilution effect. Moreover, these reservoirs exhibit lower pressure than their surrounding strata, thus facilitating helium enrichment. Consequently, shallow natural gas reservoirs with anomalously low pressures in the Sichuan Basin have the potential to emerge as play fairways for helium enrichment.